Cardiac structure and function in response to a multi-stage marathon over 4486 km. (26th October 2019) - Klenk, Christopher; Brunner, Horst; Nickel, Thomas; Sagmeister, Florian; Yilmaz, Atilgan; Infanger, Denis; Billich, Christian; Scharhag, Jürgen; Vogeser, Michael; Beer, Meinrad; Schütz, Uwe; Schmidt-Trucksäss, Arno
Abstract: Aims: To investigate whether participation in the Trans Europe Foot Race 2009 (TEFR), an ultramarathon race held over 64 consecutive days and 4486 km, led to changes in cardiac structure and function. Methods: Cardiac magnetic resonance imaging was performed in 20 of 67 participating runners (two women; mean ± SD age 47.8 ± 10.4 years) at three time points (baseline scan at 294 ± 135 km (B), scan two at 1735 ± 86 km (T1) and scan three at 3370 ± 90 km (T2)) during the TEFR. Imaging included an assessment of left ventricular structure (mass) and function (strain). In parallel, cardiac troponin I, NT-pro-BNP, myostatin and GDF11 were determined in venous blood samples. A subsample of ten runners returned for a follow-up scan eight months after the race. Results: Left ventricular mass increased significantly (B, 158.5 ± 23.8 g; T1, 165.1 ± 23.2 g; T2, 167 ± 24.6 g; p  < 0.001) over the course of the race, although no significant change was seen in the remaining structural and functional parameters. Serum concentrations of cardiac troponin I and NT-proBNP significantly increased 1.5 - and 3.5-fold, respectively, during the first measurement interval, with no further increase thereafter (cardiac troponin I, 6.8 ± 3.1 (B), 16.9 ± 10.4 (T1) and 17.1 ± 9.7 (T2); NT-proBNP, 30.3 ± 22.8 (B), 135.9 ± 177.5 (T1) and 111.2 ± 87.3 (T2)), whereas the growth markers myostatin and GDF11 did not change. No association was observed with functional parameters, including the ejection fraction and the volume of both ventricles. The follow-up scans showed a reduction to baseline values (left ventricular mass 157 ± 19.3 g). Conclusions: High exercise-induced cardiac volume load for >2 months in ultra-endurance runners results in a physiological structural adaptation with no sign of adverse cardiovascular remodelling.